Endogenous p53 inhibitor TIRR dissociates systemic metabolic health from oncogenic activity - Tsaousidou, Eva; Chrzanowski, Jędrzej; Drané, Pascal; Lee, Grace Y.; Bahour, Nadine; Wang, Zeqiu Branden; Deng, Shijun; Cao, Zhe; Huang, Kaimeng; He, Yizhou; Kaminski, Mateusz; Michalek, Dominika; et al. (Cell reports (Cambridge), 2024)
It is unclear whether metabolic health corresponds to reduced oncogenesis or vice versa. We study Tudor-interacting repair regulator (TIRR), an inhibitor of p53 binding protein 1 (53BP1)-mediated p53 activation, and the physiological consequences of enhancing tumor suppressor activity. Deleting TIRR selectively activates p53, significantly protecting against cancer but leading to a systemic metabolic imbalance in mice. TIRR-deficient mice are overweight and insulin resistant, even under normal chow diet. Similarly, reduced TIRR expression in human adipose tissue correlates with higher BMI and insulin resistance. Despite the metabolic challenges, TIRR loss improves p53 heterozygous (p53HET) mouse survival and correlates with enhanced progression-free survival in patients with various p53HET carcinomas. Finally, TIRR’s oncoprotective and metabolic effects are dependent on p53 and lost upon p53 deletion in TIRR-deficient mice, with glucose homeostasis and orexigenesis being primarily regulated by TIRR expression in the adipose tissue and the CNS, respectively, as evidenced by tissue-specific models. In summary, TIRR deletion provides a paradigm of metabolic deregulation accompanied by reduced oncogenesis. [Display omitted] •TIRR, by inhibiting p53, has opposing roles in metabolic homeostasis and oncogenesis•TIRR-deficient mice are spontaneously overweight and insulin resistant•TIRR deletion improves p53HET mouse survival, and the oncoprotective effect is p53 dependent•Low TIRR correlates with enhanced survival in patients with p53 heterozygous carcinomas Tsaousidou et al. describe opposing roles for TIRR, an inhibitor of the tumor suppressor p53. TIRR loss in mice results in increased body weight and insulin resistance but protects from cancer. Similarly, low TIRR levels correlate with increased body mass index in patients with type 2 diabetes but increased survival in patients with various carcinomas.